Commodifying Violence in Literature and on Screen The Colombian Condition - Herrero-Olaizola, Alejandro (Routledge Interdisciplinary Perspectives on Literature, 2022)
This book traverses the cultural landscape of Colombia through in-depth analyses of displacement, local and global cultures, human rights abuses, and literary and media production. Through an exploration of the cultural processes that perpetuate the "darker side" of Latin America for global consumption, it investigates the "condition" that has led writers, filmmakers, and artists to embrace (purposefully or not) the incessant violence in Colombian society as the object of their own creative endeavors. In this examination of mass-marketed cultural products such as narco-stories, captivity memoirs, gritty travel narratives, and films, Herrero-Olaizola seeks to offer a hemispheric approach to the role played by Colombia in cultural production across the continent where the illicit drug trade has made significant inroads. To this end, he identifies the "Colombian condition" within the parameters of the global economy while concentrating on the commodification of Latin America's violence for cultural consumption. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.